On the singular limit problem for nonlocal conservation laws: A general approximation result for kernels with fixed support - Keimer, Alexander; Pflug, Lukas (Journal of Mathematical Analysis and Applications, 2025)
We prove convergence of solutions of nonlocal conservation laws to their local entropic counterpart for a fundamentally extended class of nonlocal kernels when these kernels approach a Dirac distribution. The nonlocal kernels are assumed to have fixed support and do not have to be monotonic. With sharp estimates of the nonlocal kernels and a surrogate nonlocal quantity, we prove compactness in C(Lloc1) which allow passing to the limit in the weak formulation. A careful analysis of the entropy condition of local conservation laws together with the named estimators for the considered kernels enable it to prove the entropy admissibility of the nonlocal equation in the limit, completing the convergence proof.
CRIS-Team Scopus Importer:2025-02-07
Keywords: Entropy solutions; Integral kernels; Nonlocal approximation; Nonlocal conservation laws; Singular limit problem